Green Economy as a Part of Corporate Social Responsibility Management by using Sustainable Business Model Canvas - Małgorzata RUTKOWSKA; Anna Maria KAMIŃSKA (Communications of International Proceedings, 2020)
The article is devoted to concepts of green economy on the background of Corporate Social Responsibility (CSR). The purpose of this paper to evaluate the relationship between the green economy as a part of corporate social responsibility in management with the use of a business model. In this article, Osterwalder’s business model canvas is treated as a tool that supports green economy and CSR. The article uses the descriptive method as a preliminary tool. It consisted in distinguishing and describing a specific phenomenon, which is green economy and CSR. Complementary to the inductive approach, a reduction approach was used, allowing for the verification of the obtained generalizations.
Keywords: CSR; Green Economy; Sustainable Business Model Canvas